Perceived importance and attainment of managerial competencies and the relationship with motivational factors among bank managers in Melaka and Negeri Sembilan for the Year 2001- a preliminary study / Arshad Hashim, Aminah Mohd Abbas and Rachel Samuel - Hashim, Arshad; Mohd Abbas, Aminah; Samuel, Rachel (2005)
In Malaysia, the banking sector is facing tremendous challenges in the wake of the liberalization of the financial market. Bank management uses gap analysis to assess individuals and decide who should remain with the bank and who should retire through voluntary separation scheme. The question is whether in reality. do bank managers have the required competencies that they themselves perceive as important or is there a gap between what they perceive as important and what they actually attained? This study therefore is designed to investigate if there is a gap and to explore the areas where wide gaps exist. The data for this study is sourced from personal interviews carried out among the randomly selected 116 bank managers and assistant bank managers (97% response rate) in the state of Melaka and Negeri Sembilan in 2001. Questions consisting of 106 items were first tested for reliability (alpha of 98%) and analyzed. The test of significant variation between the 10 managerial competencies (communication skill, leadership, managing jobs, problem analysis, application of appropriate solution, public relations, coaching, counselling subordinates, gathering data, and customer handling) as perceived importance and attained by the respondents were all significantly different at P<O. 00. The attributes with the widest gap are customer handling, followed by gathering data/information and problem-solving skills. The attributes with the smallest gap are communication skill, leadership and coaching. It was also found that the existence of a gap between two (perceived importance and attainment for all competencies) is significantly related with perceived attainment of managerial competencies, the demographic constructs and the 10 job-related motivational factors.